Strategic Development of Agro-tourism Villages in Sungai Geringging, Kampar Regency: An Analytical Hierarchy Process (AHP) Approach - ., Eriyati; ., Thamrin; ., Nofrizal; Yoswaty, Dessy (Journal of Ecohumanism, 2024)
This study explores the strategic development of agro-tourism villages in Sungai Geringging, Kampar Regency, focusing on optimizing local natural resources and promoting sustainable tourism. Utilizing the Analytical Hierarchy Process (AHP), the research identifies key criteria for development, including natural resource potential, accessibility, socio-economic conditions, and public facilities. The findings highlight the importance of government and private partnerships in fostering agro-tourism, enhancing local infrastructure, and improving community welfare. The study concludes with recommendations for maximizing economic and social benefits through targeted tourism strategies.